Rituximab is an effective treatment in patients with pemphigus vulgaris and demonstrates a steroid‐sparing effect. (1st May 2020) - Chen, D.M.; Odueyungbo, A.; Csinady, E.; Gearhart, L.; Lehane, P.; Cheu, M.; Maho‐Vaillant, M.; Prost‐Squarcioni, C.; Hebert, V.; Houivet, E.; Calbo, S.; Caillot, F.; et al.
Summary: Background: Corticosteroids (CS) with or without adjuvant immunosuppressant agents are standard treatment for pemphigus vulgaris (PV). The efficacy of adjuvant therapies in minimizing steroid‐related adverse events (AEs) is unproven. Objectives: To utilize data collected in a French investigator‐initiated, phase III, open‐label, randomized controlled trial to demonstrate the efficacy and safety of rituximab and seek approval for its use in PV. Methods: This was an independently conducted post hoc analysis of the moderate‐to‐severe PV subset enrolled in the Ritux 3 study. Patients were randomized to rituximab plus 0·5 or 1·0 mg kg −1 per day prednisone tapered over 3 or 6 months, or 1·0 or 1·5 mg kg −1 per day prednisone alone tapered over 12 or 18 months, respectively (according to disease severity). The primary end point was complete remission at month 24 without CS (CRoff) for ≥ 2 months, and 24‐month efficacy and safety results were also reported. Results: At month 24, 34 of 38 patients (90%) on rituximab plus prednisone achieved CRoff ≥ 2 months vs. 10 of 36 patients (28%) on prednisone alone. Median total cumulative prednisone dose was 5800 mg in the rituximab plus prednisone arm vs. 20 520 mg for prednisone alone. Eight of 36 patients (22%) who received prednisone alone withdrew from treatment owing to AEs; one rituximab‐plus‐prednisone patient withdrew due to pregnancy. Overall, 24 of 36 patients (67%) on prednisone alone experienced a grade 3/4 CS‐related AE vs. 13 of 38 patients (34%) on rituximab plus prednisone. Conclusions: In patients with moderate‐to‐severe PV, rituximab plus short‐term prednisone was more effective than prednisone alone. Patients treated with rituximab had less CS exposure and were less likely to experience severe or life‐threatening CS‐related AEs. What's already known about this topic? Pemphigus vulgaris (PV) is the most common type of pemphigus. Corticosteroids, a standard first‐line treatment for PV, have significant side‐effects. Although their effects are unproven, adjuvant corticosteroid‐sparing agents are routinely used to minimize steroid exposure and corticosteroid‐related side‐effects. There is evidence that the anti‐CD20 antibody rituximab is effective in the treatment of patients with severe recalcitrant pemphigus and in patients with newly diagnosed pemphigus. What does this study add? This study provides a more detailed analysis of patients with PV enrolled in an investigator‐initiated trial. Rituximab plus prednisone had a steroid‐sparing effect and more patients achieved complete remission off prednisone. Fewer patients experienced grade 3 or grade 4 steroid‐related adverse events than those on prednisone alone. This collaboration between academia and industry, utilizing independent post hoc analyses, led to regulatory authority approvals of rituximab in moderate‐to‐severe PV.